Tetramethylpyrazine exerts neuroprotective effects in a mouse model of acute hypobaric hypoxia - Lan, Xiong; Zhou, Wei; Zhou, Lei; Deng, Huifang; Shen, Pan; Bai, Zhijie; Huangfu, Chaoji; Wang, Ningning; Sun, Yue; Xiao, Chengrong; Ma, Zengchun; Zhang, Pengfei; et al. (Frontiers in Pharmacology, 2025)
IntroductionCognitive impairment is a common issue for individuals ascending to high-altitude regions, and there is currently a lack of effective preventive or therapeutic medications. Tetramethylpyrazine (TMP), a small-molecule compound with blood-brain barrier permeability, has shown neuroprotective effects in various neurological disorders. This study aimed to investigate its potential protective role against hypoxia-induced cognitive deficits.MethodsThe neuroprotective effects of TMP were evaluated both in vivo and in vitro. A simulated high-altitude hypobaric hypoxia mouse model was used to assess survival, cognitive function, cerebral ATP levels, and hippocampal histopathology. In vitro studies were conducted to examine hypoxia-induced neuronal death using primary neurons and HT22 cells. Furthermore, mechanistic investigations were performed to identify the molecular target of TMP and its functional impact.ResultsTMP treatment significantly prolonged survival and alleviated cognitive impairment in mice exposed to hypobaric hypoxia. It also elevated cerebral ATP levels and reduced hippocampal cellular edema. In vitro, TMP reduced hypoxia-induced neuronal death. Mechanistically, TMP was identified to potentially bind to the ion channel protein KCNK2 (TREK-1) and inhibit TREK-1-mediated current.DiscussionOur findings demonstrate that TMP provides significant neuroprotection under hypobaric hypoxia conditions. The mechanism is linked, at least in part, to the inhibition of the TREK-1 channel. These results position TMP as a promising therapeutic candidate for preventing or treating high-altitude-induced cognitive dysfunction.